Analysis of the Effects of MCQ Enthusiasm, Attendance, Discussion Activeness, and Test Completion on Essay Success in Online Leadership Learning - Arief Hamdani Gunawan; Siswantoyo Siswantoyo (Eduvest - Journal of Universal Studies, 2026)
Evaluating the effectiveness of leadership learning for senior-level employees (one level below the director) presents unique challenges in measuring competencies. This research aims to analyze the predictive validity of various instruments of online learning activities on the strategic competence of participants, as measured through the success of essay preparation. The predictive variables tested included: (1) Enthusiasm for working on the Multiple Choice Question (MCQ), (2) Attendance of Kick-Off Meeting, (3) Attendance of Online Sessions, (4) Activity of Discussions, (5) Completion of Reaction Test, and (6) Completion of Learning Test. The study involved 40 senior employees from various companies. Data were analyzed using Binary Logistic Regression. The results showed that the regression model explained 63% of the variance in essay success. Key findings revealed that administrative variables (attendance) and procedural cognitive tests (MCQs) did not have a significant influence on essay success. The only variable proven to have a significant effect was Discussion Activity (Sig < 0.05), with an Odds Ratio of 19.3. This indicates that, for executive-level learners, leadership competencies are more validly predicted through the dialectic of arguments in discussions rather than mere presence or memorization of theory.